2011
DOI: 10.1378/chest.10-2885
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Lymph Node Metastases as a Prognostic Factor in Patients With N1 Non-small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer mortality for both men and women in the United States. 1 The overall 5-year survival rate for the disease is only 16%, but patients with resected non-small cell lung cancer (NSCLC) have a considerably better prognosis. 2 Staging is a critical aspect of the diagnostic workup of lung cancer as it infl uences treatment decisions and allows accurate communication about prognosis to patients and their families. Lymph node (LN) status is a key component of the lung cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 27 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…Although the N descriptors in the new edition of TNM system were not changed, several studies have reported that, within the N1 category, there are several prognostic modifiers. These include the number of lymph nodes involved (solitary versus multiple) [19][20][21], the ratio of lymph nodes involved [20,21], the level of lymph nodes involved (hilar versus lobar) [7,11,12,22,23], and the pattern of lymph nodes involved (direct invasion versus separate metastases) [24,25]. Several studies have highlighted that N1 disease represents a heterogeneous group of patients with different lymph node-related factors affecting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the N descriptors in the new edition of TNM system were not changed, several studies have reported that, within the N1 category, there are several prognostic modifiers. These include the number of lymph nodes involved (solitary versus multiple) [19][20][21], the ratio of lymph nodes involved [20,21], the level of lymph nodes involved (hilar versus lobar) [7,11,12,22,23], and the pattern of lymph nodes involved (direct invasion versus separate metastases) [24,25]. Several studies have highlighted that N1 disease represents a heterogeneous group of patients with different lymph node-related factors affecting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches for the evaluation of LN management during lung resection include the number of resected LN, the LN ratio (LNR), the number of resected LN stations, and nodal upstaging (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of metastatic LNs may be more important than the total number of dissected LNs. Previous studies reported that the number of metastatic LNs can predict the outcome after NSCLC complete resection, and that this is a strong independent prognostic factor (15,24,25). It was suggested that this approach provides more accurate pathologic nodal staging then the method of considering the anatomical location of involved LNs (26).…”
Section: Discussionmentioning
confidence: 99%
“…Saji et al found that four or more affected LNs were a good indicator of outcome after surgery (25). Jonnalagadda et al also reported that the number of affected LNs was an independent prognostic factor for overall survival in patients with N1 NSCLC (15). However, all previous studies analyzed the data with the Cox proportional hazards model, with adjustment for other potential prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation